The Vietnam project: developing conceptual knowledge on cross-cultural skills for training in SME internationalization. Issue 3 (27th May 2019) - Selvarajah, Christopher; Le, Tien Dat; Sukunesan, Suku
ABSTRACT: This paper explores the importance of cross-cultural skills needed by Vietnamese SMEs (current and potential) exporters across Hanoi, Da Nang and Ho Chi Minh City (HCMC). The findings suggest that training needs vary by regions, stage of SME development and cultural context of the region. The study has both theoretical and practical implications. The paper suggests that prior to designing and implementing training, the identification process must involve systematic conceptualization of key export stimuli and be informed by best practice and empirical knowledge. The study endeavours to develop a conceptual framework and propositions for future research.